A novel G6PC3 gene mutation in severe congenital neutropenia: pancytopenia and variable bone marrow phenotype can also be part of this syndrome. (13th May 2014) - Arikoglu, Tugba; Kuyucu, Necdet; Germeshausen, Manuela; Kuyucu, Semanur
Abstract Glucose‐6‐phosphatase catalytic subunit 3 (G6PC3) deficiency is a newly described syndrome characterized by severe congenital neutropenia associated with multiple organ abnormalities including cardiac and urogenital malformations. The underlying pathophysiology of increased apoptosis of myeloid cells and of neutrophil dysfunction in G6PC3 deficiency involves disturbed glucose metabolism, increased endoplasmic reticulum stress and deficient protein folding. Here, we report a new case of G6PC3 deficiency caused by a novel homozygous G6PC3 gene mutation p.Trp59Arg. The patient showed pancytopenia and a variable bone marrow phenotype with maturation arrest and vacuolization in myeloid lineage cells and a normocellular marrow, respectively. She also showed persistent lymphopenia with low CD4 T‐ and CD19 B‐cell counts. Lymphopenia and even pancytopenia as well as a variable bone marrow phenotype can be part of this syndrome. These clinical findings in a patient with chronic neutropenia should alert the clinician to consider a diagnosis of G6PC3 deficiency.